Traversing the Persian Gauntlet: U.S. Naval Projection and the Strait of Hormuz - Gresh, Geoffrey F. (Tufts Archival Research Center, 2005)
Volume 34, Issue 1. Winter Geoffrey Gresh, a PhD candidate at the Fletcher School of Law and Diplomacy, explores the geopolitical significance of the Straits of Hormuz- the narrow waterway connecting the Persian Gulf with the Arabian Sea-and its implications for U.S. naval policy in the region. Despite potential threats from Iran and al-Qaeda, he argues that a robust U.S. naval presence is not necessary to protect the Straits and that U.S. national security interests in the Gulf can be met with a much smaller naval deployment and increased cooperation with regional allies.